2020
DOI: 10.1101/2020.07.30.229880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Memory drives the formation of animal home ranges: evidence from a reintroduction

Abstract: Most animals live in a characteristic home range, a space-use pattern thought to emerge from the benefits of memory-based movements; however, a general model for characterizing and predicting their formation in the absence of territoriality has been lacking. Here, we use a mechanistic movement model to quantify the role of memory in the movements of a large mammal reintroduced into a novel environment, and to predict observed patterns of home range emergence. We show that an interplay between memory and resour… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
2
14
0
Order By: Relevance
“…In their opportunistic use of the food provided at feeding sites, roe deer confirm their high behavioral and ecological plasticity [ 67 ], which is further supported by the observed drastic decrease of visits to feeding sites when supplemental food was not accessible i.e., during the experimental “closure” of feeding sites. The underlying process supporting such behavioral plasticity likely relies on memory, which allows individuals to profitably track spatio-temporal alteration of resource availability [ 16 , 68 , 69 ]. Interestingly, the seasonal pattern of feeding site use that we describe, and space use and movement behavior around feeding sites [ 15 ] varied between roe deer individuals with different degrees of preference for supplemental feeding, supporting the general principle that foraging behavior in mammals may vary widely between individuals [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their opportunistic use of the food provided at feeding sites, roe deer confirm their high behavioral and ecological plasticity [ 67 ], which is further supported by the observed drastic decrease of visits to feeding sites when supplemental food was not accessible i.e., during the experimental “closure” of feeding sites. The underlying process supporting such behavioral plasticity likely relies on memory, which allows individuals to profitably track spatio-temporal alteration of resource availability [ 16 , 68 , 69 ]. Interestingly, the seasonal pattern of feeding site use that we describe, and space use and movement behavior around feeding sites [ 15 ] varied between roe deer individuals with different degrees of preference for supplemental feeding, supporting the general principle that foraging behavior in mammals may vary widely between individuals [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal memory provides a plausible biological explanation of this phenomenon and recent empirical evidence supports this hypothesis (Merkle et al 2014;Bracis & Mueller 2017;Merkle et al 2017;Ranc et al 2020a;Ranc et al 2021). While quantifying memory is particularly challenging, theoretical analyses have demonstrated that memory-based foraging processes can produce emergent home ranges and more efficient resource use, in line with the theory of optimal foraging (Van Moorter et al 2009;Bracis et al 2015;Riotte-Lambert et al 2015).…”
Section: Introductionmentioning
confidence: 81%
“…An interesting avenue for further analysis of this dataset would be to explore these alternate behavioural hypotheses for the concentration of relocations at home range edges. One approach may be to formulate a model of fine‐scale movement behaviour incorporating these effects of resources, such as redistribution kernels (Avgar et al., 2015; Ranc, Cagnacci, & Moorcroft, 2020; Schlägel & Lewis, 2014), and integrated resource selection analysis (Avgar et al., 2016), with the potential to advance our understanding of the mechanisms underlying resource selection by animals.…”
Section: Figurementioning
confidence: 99%
“…Theoretical analyses have shown that memory‐based foraging (Bracis et al., 2015; Riotte‐Lambert et al., 2015; Van Moorter et al., 2009), and memory‐based avoidance of past interactions with conspecifics (Potts & Lewis, 2016) can lead to the emergence of home ranges. In recent years, empirical evidence of the influence of memory on animal foraging decisions (Merkle et al., 2014; Ranc, Moorcroft, Ossi, & Cagnacci, 2020), and ultimately space‐use patterns (Merkle et al., 2017; Ranc, Cagnacci, & Moorcroft, 2020) has been accumulating. Ellison et al.…”
Section: Figurementioning
confidence: 99%